Tumor necrosis at FDG-PET is an independent predictor of outcome in diffuse large B-cell lymphoma. Issue 1 (January 2016) - Adams, Hugo J.A.; de Klerk, John M.H.; Fijnheer, Rob; Heggelman, Ben G.F.; Dubois, Stefan V.; Nievelstein, Rutger A.J.; Kwee, Thomas C.
Highlights: FDG-PET is frequently used for staging newly diagnosed DLBCL. Approximately 20.4% of DLBCL patients have tumor necrosis at FDG-PET. Both tumor necrosis and NCCN-IPI are associated with outcome at univariate analysis. Both tumor necrosis and NCCN-IPI are associated with outcome at multivariate analysis. Abstract: Purpose: To determine the prognostic performance of tumor necrosis at FDG-PET in patients with newly diagnosed diffuse large B-cell lymphoma (DLBCL) who are treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) therapy. Materials and methods: 108 patients with newly diagnosed DLBCL who underwent FDG-PET before R-CHOP therapy were retrospectively included. Lymphomatous sites at FDG-PET were assessed for the presence of a photopenic area, in keeping with tumor necrosis. Univariate and multivariate Cox regression analyses were performed to determine the associations of tumor necrosis and National Comprehensive Cancer Network International Prognostic Index (NCCN-IPI) with progression-free survival (PFS) and overall survival (OS). Results: On univariate Cox regression analysis, both tumor necrosis and higher NCCN-IPI risk groups were significantly associated with PFS ( P  = 0.024 and P  < 0.001, respectively) and OS ( P  = 0.034 and P  < 0.001, respectively). On multivariate Cox regression analysis, both tumor necrosis and the NCCN-IPI were independent significant predictors for PFS ( P  = 0.007, hazard ratio: 2.723 [95% confidence interval: 1.324–5.597] and P  < 0.001, hazard ratio: 2.952 [95% confidence interval: 1.876–4.646], respectively) and OS ( P  = 0.009, hazard ratio: 2.794 [95% confidence interval: 1.305–5.985] and P  < 0.001, hazard ratio: 2.813 [95% confidence interval: 1.724–4.587], respectively). Conclusion: Tumor necrosis at FDG-PET is an NCCN-IPI-independent predictor of outcome in DLBCL.